Transformasi Kurikulum dalam Menghadapi Tantangan Pendidikan Abad 21 - Cahyaningsih, Ayu; Ramadhani, Layla; Aulia, Hanifah; Alwi, Nur Azmi; Ningsih, Yarisda (Jurnal Nakula : Pusat Ilmu Pendidikan, Bahasa dan Ilmu Sosial, 2025)
Technological developments and changes in the global world are driving rapid transformation in various aspects.The education system needs to undergo fundamental changes to prepare the next generation to face the challenges and opportunities of the 21st century. A new curriculum needs to be designed to teach students the essential skills of this century, such as critical thinking, creativity, collaboration, and understanding digital literacy. The conventional curriculum model that focuses on mastering factual knowledge and basic skills is no longer sufficient.In order to change education, all aspects of the education ecosystem must be evaluated comprehensively, including the government, educational institutions, teachers, parents, and society as a whole. The curriculum must be updated to support project-based learning methods, cross-disciplinary research, and an emphasis on developing 21st century skills. In addition, the way of teaching must shift from a teacher-dominated approach to a student-focused approach, with the help of digital technology.